“Cartoonia hospital”. Skin disorders and films for children. - Cutrone, M. (European Journal of Pediatric Dermatology, 2003)
The Author discusses the utilization of skin disorders in the cinema literature to connote a character as good or bad. Particularly, the use of nevi, alopecia and piebaldism is discussed. Nevi and piebaldism are usual marker of the bad character. On the other hand, alopecia, mainly in childhood films, is used to connote a good character.